The influence of the equivalent hydraulic diameter on the pressure drop prediction of annular test section - Al-Kayiem, A.H.H. (Institute of Physics Publishing, 2015)
The flow behaviour and the pressure drop throughout an annular flow test section was investigated in order to evaluate and justify the reliability of experimental flow loop for wax deposition studies. The specific objective of the present paper is to assess and highlight the influence of the equivalent diameter method on the analysis of the hydrodynamic behaviour of the flow and the pressure drop throughout the annular test section. The test section has annular shape of 3 m length with three flow passages, namely; outer thermal control jacket, oil annular flow and inner pipe flow of a coolant. The oil annular flow has internal and external diameters of 0.0422 m and 0.0801 m, respectively. Oil was re-circulated in the annular passage while a cold water-glycol mixture was re-circulated in the inner pipe counter currently to the oil flow. The experiments were carried out at oil Reynolds number range of 2000 to 17000, covering laminar, transition and turbulent flow regimes. Four different methods of equivalent diameter of the annulus have been considered in this hydraulic analysis. The correction factor model for frictional pressure drop was also considered in the investigations. All methods addressed the high deviation of the prediction from the experimental data, which justified the need of a suitable pressure prediction correlation for the annular test section. The conventional hydraulic diameter method is a convenient substitute for characterizing physical dimension of a non-circular duct, and it leads to fairly good correlation between turbulent fluid flow and heat transfer characteristic of annular ducts.